Analisis Kriminologi Terhadap Kasus Pembunuhan (Studi Kasus: Terhadap Naufal Zidan Mahasiswa Universitas Indonesia) - Mohamad Revaldy Fairuzzen; Abil Arya Putra; Akmal Reihan; Dr.Hj.Asmak Ul hosnah,SH.MH (Indonesian Journal of Islamic Jurisprudence, Economic and Legal Theory, 2024)
Abstract: Criminology is an object of study that examines the meaning of crime from a social perspective. The study of criminal incidents is interesting to analyze from a criminological perspective for several reasons: firstly, criminological studies are expected to explain the extent to which the growth rate of crime is high in society. Second, that legal conflict does not only occur because of the normative factors of law itself, but is also influenced by the presence of triggering factors outside the law, such as poverty, social problems, and so on. On this occasion, researchers used the murder case that happened to Naufal Zidan, who was a student at the University of Indonesia who was killed by his senior. Keywords: Criminology, Murder Abstrak: Kriminologi menjadi fokus studi yang mengeksplorasi makna kejahatan dari perspektif sosial. Analisis kejadian kriminal dari sudut pandang kriminologi menjadi menarik karena beberapa alasan: pertama, studi kriminologi diharapkan dapat menjelaskan sejauh mana tingkat pertumbuhan angka kejahatan di masyarakat. Kedua, pemahaman tentang pelanggaran hukum tidak hanya terkait dengan norma-norma hukum semata, tetapi juga dipengaruhi oleh faktor-faktor eksternal seperti kemiskinan, masalah sosial, dan sebagainya. Dalam konteks ini, peneliti memilih untuk menganalisis kasus pembunuhan Naufal Zidan, seorang mahasiswa Universitas Indonesia yang tewas dibunuh oleh seniornya. Kata kunci: Kriminologi, Pembunuhan